Impact of Covid19 and its Treatment: A Report - Veer, Karan; Sharma, Tanu (Current Signal Transduction Therapy, 2021)
Till now, across from a few basic data, nothing is well clear regarding its exact origin, incubation period, seriousness and what makes it transmissible is not recommended for COVID19 anywhere in the world. It was on 28 January, 2020 that the World Health Organisation released a paper relating to medical data and recommendations from the management of previous HCoV epidemics. The present paper outlines steps for the identification and assessment of patients with extreme acute respiratory disease; monitoring and infection prevention strategies; tracking and early intervention therapy; treatment of respiratory arrest and ARDS; clinical diagnosis; recommendations for septic shock management; therapies; and concerns for pregnant women.
Keywords: drugs